2017
DOI: 10.1186/s13287-017-0612-4
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle-derived interstitial progenitor cells (PICs) display stem cell properties, being clonogenic, self-renewing, and multi-potent in vitro and in vivo

Abstract: BackgroundThe development of cellular therapies to treat muscle wastage with disease or age is paramount. Resident muscle satellite cells are not currently regarded as a viable cell source due to their limited migration and growth capability ex vivo. This study investigated the potential of muscle-derived PW1+/Pax7– interstitial progenitor cells (PICs) as a source of tissue-specific stem/progenitor cells with stem cell properties and multipotency.MethodsSca-1+/PW1+ PICs were identified on tissue sections from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
1
24
0
1
Order By: Relevance
“…MDSCs are a heterogeneous mixture of cells with variable proliferation and differentiation potentials; currently, no standard marker has been set for MDSCs, and more work thus needs to be performed to establish differences and similarities between the various populations. The more recent characterization of MDSCs by various groups has identified a panel of cellular markers to distinguish MDSCs from other muscle originated progenitor cells including SCs, pericytes, and interstitial progenitor cells [33,58,59]. Our data aligned with literature that the isolated MDSCs showed high expression in CD105 and Sca-1, whereas low expression in CD4 and CD45; it also showed negative staining for the SCspecific marker PAX7, the pericyte-specific marker CD146, and interstitial progenitor cell marker PW1.…”
Section: Discussionsupporting
confidence: 86%
“…MDSCs are a heterogeneous mixture of cells with variable proliferation and differentiation potentials; currently, no standard marker has been set for MDSCs, and more work thus needs to be performed to establish differences and similarities between the various populations. The more recent characterization of MDSCs by various groups has identified a panel of cellular markers to distinguish MDSCs from other muscle originated progenitor cells including SCs, pericytes, and interstitial progenitor cells [33,58,59]. Our data aligned with literature that the isolated MDSCs showed high expression in CD105 and Sca-1, whereas low expression in CD4 and CD45; it also showed negative staining for the SCspecific marker PAX7, the pericyte-specific marker CD146, and interstitial progenitor cell marker PW1.…”
Section: Discussionsupporting
confidence: 86%
“…In vitro studies showed that they start expressing Pax7/MyoD prior to formation of MHC-positive myotubes through fusion with other PICs or through fusion to satellite cell-derived myotubes [137,138]. When transplanted into a regenerating muscle, PICs contribute to the formation of new muscle fibers at a level comparable to transplanted satellite cells [137,139]. Not only do they contribute to muscle fiber formation during regeneration of skeletal muscle, but also secrete factors such as FGF-2 and IGF-1, known to promote satellite cell functionality [140].…”
Section: Non-myogenic Cells Involved In Regeneration Of Skeletal Musclementioning
confidence: 99%
“…Stem/progenitor cells isolated from murine and human skeletal muscles by various methods give rise to progeny cells with neuronal and glial phenotypes . Muscle‐derived stem cells (MDSCs) were our first choice of seed cells attributed to the strong capacity of self‐renewal, multipotent differentiation, and immune‐privileged behavior, which was reported to successfully promote PNI recovery . According to reported studies, MDSCs have the potential to undergo multilineage differentiation, such as myogenic, neural, osteogenic, and hematopoietic lineages .…”
Section: Introductionmentioning
confidence: 99%